Emicizumab, A Bispecific Antibody to Factors IX/IXa and X/Xa, Does Not Interfere with Antithrombin or TFPI Activity In Vitro - Noguchi-Sasaki, Mariko; Soeda, Tetsuhiro; Ueyama, Atsunori; Muto, Atsushi; Hirata, Michinori; Kitamura, Hidetomo; Fujimoto-Ouchi, Kaori; Kawabe, Yoshiki; Nogami, Keiji; Shima, Midori; Kitazawa, Takehisa (TH Open, 2018)
Emicizumab is a humanized bispecific antibody that binds simultaneously to factor (F) IXa and FX replacing the cofactor function of FVIIIa. Because emicizumab recognizes FIX/FIXa and FX/FXa, a question may arise whether emicizumab competes with antithrombin (AT) and/or tissue factor pathway inhibitor (TFPI), thereby enhancing overall hemostatic potential by blocking their antihemostatic effects. To address this question, we performed enzymatic assays using purified coagulation factors to confirm whether emicizumab interferes with the action of AT on FIXa or FXa, or with the action of TFPI on FXa. In those assays, we found no interference of emicizumab on the actions of AT and TFPI. We next assessed emicizumab's influences on the anticoagulation actions of AT or TFPI in thrombin generation assays triggered with FXIa or tissue factor (TF) in AT-depleted or TFPI-depleted plasma supplemented with AT or TFPI in vitro. In those assays, we employed anti-FIXa and anti-FX monospecific one-armed antibodies derived from emicizumab instead of emicizumab itself so as to prevent emicizumab's FVIIIa cofactor activity from boosting thrombin generation. Consequently, we found that neither anti-FIXa, anti-FX monospecific antibody, nor the mixture of the two interfered with the anticoagulation actions of AT or TFPI in plasma. Although emicizumab can bind to FIXa and FXa, our results showed no interference of emicizumab with the action of AT or TFPI on FIXa or FXa. This indicates that the presence of emicizumab is irrelevant to the action of AT and TFPI, and thus should not alter the coagulant/anticoagulant balance related to AT and TFPI.
Keywords: emicizumab; antithrombin; TFPI; coagulation factors; hemophilia A